Characterization of the complete chloroplast genome of Liquidambar acalycina Chang. Issue 2 (2nd April 2020) - Lai, Jiu-Xin; Lin, Fu-Rong; Huang, Ping; Li, Chang-Hong; Zheng, Yong-Qi
Abstract: Liquidambar acalycina is a popular tree species with high ornamental and economic values because of the leaf shape and coloration. In this study, chloroplast genome of L.acalycina was assembled using Illumina highlights pair-end sequencing data. The chloroplast genome has a quadripartite structure with 160, 433 bp in length. It contains a pair of 26, 274 bp inverted repeat (IR) regions, which were separated by large single-copy (LSC: 88, 963bp) region and small single-copy (SSC: 18, 922 bp) region. A total of 133 genes were annotated, including 88 protein-coding genes (PCGs), 37 tRNAs, and 8 rRNAs. The overall GC content was 36.1%. The phylogenetic analysis revealed that L. acalycina has a close relationship with L. fomosana . This complete chloroplast genome is of great value in the genetic research of L. acalycina.